The First Labour Hospital (London : Co-operative Printing Society Ltd., 1921)
1921 1921 1920s 8 pages 8 and special treatment. The grounds and surroundings are magnificent, and I sincerely trust that all Trade Unions will do their best to see that the effort now being made will achieve a glorious success. "Yours very sincerely, "(Signed) CHARLES DUNCAN, "General Secretary." " LONDON SOCIETY of COMPOSITORS, "St. Bride Street, E.C., "7th June, 1921. "DEAR MR. BRUCE, "The taking over of the Manor House Hospital with its equipment and staff, as a going concern, for the use of the Labour Movement is an admirable example of direct action of the right sort. Having seen the Hospital, I realise its possibilities, in the treatment of compensation cases especially, and trust that it will prove to be the beginning of a greater scheme for the creation of a brand new Ministry of Health. "Yours truly, "(Signed) T.E. NAYLOR, "General Secretary." "HOUSE OF COMMONS, "June, 1921. "DEAR MURRAY BRUCE, "Very many thanks to yourself and the staff for the splendid way in which you laid everything open for our inspection. There was nothing of the 'charity ward' or of the all too common 'barrack room' attitude in any part of the administration of the Hospital. The treatment is thorough, not the partial recovery that too often sends a man back to work unfit to do his best. The massage treatment, electric baths, and the complete X Ray apparatus all proved to me that a long-felt want is now provided to give a worker a complete cure free from the taint of charity. It is, indeed, the first Labour Hospital where to cure is a labour of love "Yours sincerely, "(Signed) JACK MILLS." CONCLUSION. All who are interested in this new Movement, which is not a visionary idea but a successfully-working scheme, are invited to write to the General Secretary and make an appointment to come and see the cures that are being effected, and obtain first hand detailed knowledge of facts. J. MURRAY BRUCE, General Secretary, Manor House Hospital, North End Road, Golder's Green, N. W. 11. HOSPITAL TELEPHONE: HAMPSTEAD, 7650 NEAREST STATION: GOLDER'S GREEN To suit convenience, appointments may also be made at the London Office, 14, Leicester Street, Leicester Square, W.C. 2. Telephone: Regent, 2350. 36/H24/15